Hubungan Tingkat Pengetahuan Remaja Tentang COVID-19 dengan Sikap Remaja dalam Menerapkan Protokol Kesehatan di Masa Pandemi CoVID-19 - Putu Maya Oktavianti; N.L.K Sulisnadewi; Ida Erni Sipahutar (Jurnal Gema Keperawatan, 2021)
COVID-19 is already happening all over the world, including Indonesia. Prevention of COVID-19 can be suppressed with a good level of knowledge and a positive attitude towards youth. Study aims determine relationship between level of adolescent knowledge about COVID-19 with adolescent attitudes in implementing health protocols during COVID-19 pandemic.This type of research is non-experimental with correlational draft and design cross sectional. The sample in this study amounted to 90 people using probability sampling techniques, namely simple random sampling. Data was collected using questionnaire via whatsapp using google from. Results showed that highest age 13 years (43.3%), highest gender female (53.3%), level of adolescent knowledge about COVID-19 good (88.9%) and attitude of adolescents in implementing health protocols during COVID-19 pandemic classified positive (84.4%). Hypothesis testing used Spearman rank with value p = 0.000 (α = 0.05) and value r = 0.726. The is strong, positive and significant relationship between level of knowledge of adolescents about COVID-19 and attitude of adolescents in implementing health protocols during COVID-19 pandemic. Respondents are expected to able to sort information circulating about COVID-19 which is good and true and comes from trusted sources, so that respondents know and can apply health protocols properly and correctly.